Effects of naphthoxy side groups on functionalities of linear polyphosphazenes: Fluorescence, ion response and degradability. (16th March 2020) - Wu, Shaojun; Lin, Husitu; Zhang, Shuangkun; Liu, Wei; Liu, Jianjun; Wu, Zhanpeng; Wu, Dezhen
Abstract: Polyphosphazenes with different substitution rates of β-naphthoxy side groups are synthesized through ring opening polymerization of hexachlorocyclotriphosphazene (HCCP), subsequent nucleophilic substitution by β-naphthol in organic solutions. The concentration and solvent effects, ions response, solid-state fluorescence and degradability of these polymers are investigated. It is found that the peaks in excitation spectra redshift with the increase of polymer concentration, and gradually stronger interaction of polymer molecules results in different concentration effects at λex = 300 nm and λex = 355 nm, respectively. It demonstrates that the fluorescence intensity of polymer solution enhance by increasing the polarity of solvents, and iron ions could quench fluorescence of polymer solutions. Moreover, the fluorescence intensities of polyphosphazenes containing β-naphthoxy side groups in solid-state is stronger than those in solution. The highest fluorescence intensities of those in both solid and solution is those polymers with 90% substitution rate of naphthoxy side groups. However, the polymers with lower substitution rate of naphthoxy side groups are degradable easily in acid medium. Graphical abstract: Image 1 Highlight: Soluble, processable and precise structural fluorescence poly(bis-naphthoxy)phosphazenes were prepared The polymer shows excellent fluorescence intensity when substitution rate of naphthoxy is 90% Poly(bis-naphthoxy)phosphazenes show excellent fluorescence intensity both in solid state and solution without any aggregation-caused quenching effects The poly(bis-naphthoxy)phosphazenes have obvious response ability to iron ions and show controllable degradability